2001
DOI: 10.1136/ard.60.4.391
|View full text |Cite
|
Sign up to set email alerts
|

Down regulation of interleukin 1beta production in human osteoarthritic synovial tissue and cartilage cultures by aminoguanidine

Abstract: Objective-To evaluate the eVect of aminoguanidine (AG) on de novo interleukin 1 (IL1 ), nitric oxide (NO), and interleukin 1 receptor antagonist (IL1ra) production by osteoarthritic human synovial tissue and articular cartilage cultures. Methods-Synovial tissue and cartilage, obtained during surgery from 29 patients undergoing total knee or hip replacement for osteoarthritis, were cut into small pieces and cultured in the presence or absence of lipopolysaccharide (LPS) and test materials. IL1 , IL1ra, and NO w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…It is unclear if the lower expression of IL-1b in reIL-1b treated synovium is due to a lack of or minimal endogenous IL-1b production at PIH 8 that follows reIL-1b injection. Previous in vitro studies have reported LPS-induced IL-1b production in human OA synovial tissue and cartilage 39,40 ; however measurements were of protein concentrations and not gene expression. Exogenous IL-1b is rapidly cleared from the joint and does not stimulate endogenous production of IL-1b 21 , possibly allowing for a more representative evaluation of mediator response to IL-1b.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear if the lower expression of IL-1b in reIL-1b treated synovium is due to a lack of or minimal endogenous IL-1b production at PIH 8 that follows reIL-1b injection. Previous in vitro studies have reported LPS-induced IL-1b production in human OA synovial tissue and cartilage 39,40 ; however measurements were of protein concentrations and not gene expression. Exogenous IL-1b is rapidly cleared from the joint and does not stimulate endogenous production of IL-1b 21 , possibly allowing for a more representative evaluation of mediator response to IL-1b.…”
Section: Discussionmentioning
confidence: 99%
“…It is the only AGE inhibitor that has been studied in tissue from individuals with OA. Aminoguanidine decreased lipopolysaccharide-stimulated interleukin-1-beta and nitric oxide release from cultures of human synovial tissue and articular cartilage, obtained during total hip or knee arthroplasty surgery from patients with OA [51]. Aminoguanidine treatment also prevents AGE crosslink formation [52].…”
Section: Inhibitors Of Advanced Glycation Endproduct Formation and Crmentioning
confidence: 97%
“…sues, elevated levels of IL-1 have been found in synovial fluids from patients with OA, indicating it may be generated by cells resident in joint tissues [3,4,31]. Although mRNA's coding for the two IL-1 isoforms (IL-1a & IL-1b) were isolated from human chondrocytes [32], the relative abundance of IL-1a and IL-1b protein is less clear [33].…”
Section: Figmentioning
confidence: 99%
“…The expression of inducible MMPs (MMPs 1, 3,9,13) in cartilage is strongly stimulated by inflammatory cytokines, such as IL-1b and TNF-a. In RA, high levels of MMPs are found in synovial fluid, cartilage, and invasive synovial pannus [16][17][18].…”
Section: Introductionmentioning
confidence: 99%